Pengembangan Sistem Informasi Geografis untuk Mendukung Keputusan Perencanaan Desa Wisata - Dedy Kurnia Sunaryo; Fransiscus Xaverius Ariwibisono; Sujianto Sujianto; Biyyubahy Abdiellah Purwa Adji (STMIK Banjarbaru, 2026)
Village tourism development was considered a strategic approach to achieving sustainable development by utilizing ecological, social, and cultural potentials inherent in rural areas through community-based tourism. This study evaluated the role of high-accuracy topographic data integrated into a geographic information system as a decision support system for village tourism development planning. Field surveys were conducted in Sukorejo, Pongangan, and Ploso villages using geodetic global positioning system observations, Total Station measurements, and detailed situational mapping. The collected spatial data were processed into topographic and thematic maps to support spatial analysis and decision-making. The results showed that the integration of precise topographic data significantly improved spatial zoning accuracy, accessibility planning, and identification of development potential and environmentally vulnerable areas. This study concluded that a geographic information system-based decision support system strengthened evidence-based planning and supported sustainable village tourism development from social, economic, and environmental perspectives.Keywords: Community-Based Tourism; Decision support system; Geographic information system; Topographic mapping; Spatial planning AbstrakPengembangan desa wisata dipandang sebagai pendekatan strategis untuk mewujudkan pembangunan berkelanjutan melalui pemanfaatan potensi ekologis, sosial, dan budaya desa berbasis partisipasi masyarakat. Penelitian ini mengevaluasi peran data topografi berakurasi tinggi yang diintegrasikan ke dalam Sistem Informasi Geografis sebagai Sistem Pendukung Keputusan yang mendukung perencanaan pengembangan desa wisata. Survei lapangan dilakukan di Desa Sukorejo, Pongangan, dan Ploso menggunakan sistem geodetik, pengukuran Total Station, dan pemetaan detail situasi. Data spasial yang diperoleh diolah menjadi peta topografi dan peta tematik untuk mendukung analisis spasial dan pengambilan keputusan. Hasil penelitian menunjukkan bahwa integrasi data topografi presisi tinggi meningkatkan ketepatan penataan ruang, perencanaan aksesibilitas, serta identifikasi zona potensial dan area rentan. Penelitian ini menyimpulkan bahwa Sistem Informasi Geografis berbasis Sistem Pendukung Keputusan berperan penting dalam mendukung perencanaan desa wisata yang berkelanjutan.